2009
DOI: 10.2741/3411
|View full text |Cite
|
Sign up to set email alerts
|

Tollip attenuated the hypertrophic response of cardiomyocytes induced by IL-1beta

Abstract: We examined the role of Tollip in the hypertrophic response of cardiomyocytes. C57BL/6 mice were subjected to transverse aortic constriction (TAC) for 2 weeks and age-matched sham surgical operated mice served as control. TAC significantly reduced the association of Tollip with IRAK-1 by 66.4 percent and increased NF-kappaB binding activity by 86.5 percent and the levels of phospho-p38 by 114.6 percent in the myocardium compared with sham control, respectively. In vitro experiments showed that IL-1beta stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“… 46 It is also reported that IL‐1β can induce hypertrophic response in cardiomyocytes. 47 In addition, our data show that fatVHL1Ako mice have the highest serum levels of the biologically active IL‐12p70, suggesting a potentially important role of IL‐12p70 in exacerbating the pathological conditions induced by adipocyte HIF activation. It is, however, worth noting that, although being associated with inflammatory heart diseases, 48 elevated serum levels of IL‐6, IFNγγ, and TNFα are not critically involved in the development of fatal cardiac hypertrophy and dysfunction in fatVHL1Ako mice.…”
Section: Discussionmentioning
confidence: 64%
“… 46 It is also reported that IL‐1β can induce hypertrophic response in cardiomyocytes. 47 In addition, our data show that fatVHL1Ako mice have the highest serum levels of the biologically active IL‐12p70, suggesting a potentially important role of IL‐12p70 in exacerbating the pathological conditions induced by adipocyte HIF activation. It is, however, worth noting that, although being associated with inflammatory heart diseases, 48 elevated serum levels of IL‐6, IFNγγ, and TNFα are not critically involved in the development of fatal cardiac hypertrophy and dysfunction in fatVHL1Ako mice.…”
Section: Discussionmentioning
confidence: 64%
“…This molecule is ubiquitously expressed, with particularly high expression levels in the heart (Liu et al ., ). Studies from our group and others recently reported that Tollip negatively regulates pathological cardiac hypertrophy in vivo and in vitro (Hu et al ., ; Liu et al ., ), suggesting a critical role for Tollip in heart disease. However, despite pressure overload and myocardial ischaemia being major contributors to heart failure, distinct pathological processes participate in cardiac hypertrophy and MI (Heineke and Molkentin, ; Heusch et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory properties of TMP have been reported to involve the suppression of pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α) and interleukin-1β (8). These cytokines have been implicated in the pathogenesis of cardiac hypertrophy (10,11). However, the effects of TMP on cardiac hypertrophy and the expression of TNF-α in cardiomyocytes remain unclear.…”
Section: Introductionmentioning
confidence: 99%